Effect of lactic acid bacteria and wheat bran on the fermentation quality and bacterial community of Broussonetia papyrifera silage - Ningwei Wang; Yan Wang; Yanli Lin; Gang Xu; Kuikui Ni; Fuyu Yang (Chemical and Biological Technologies in Agriculture, 2023)
Abstract Background Paper mulberry has been considered as a high-quality protein feedstuff to cope with the shortage of feed and the development of livestock. In addition, the features of high moisture and low water-soluble carbohydrate concentration in fresh paper mulberry make it difficult to ensile. Therefore, it is important to find an optimal way to improve the paper mulberry silage quality. In this study, we aimed to investigate the application of Lactobacillus plantarum (LP) and wheat bran (WB) on the fermentation characteristics, chemical composition and microbial community of paper mulberry silage. Results The objective of this study was to evaluate the effects of Lactobacillus plantarum and wheat bran alone or combination (LP + WB) addition on the fermentation quality and bacterial community of paper mulberry silage. After 60 days of ensiling, the employed three treatments had higher crude protein contents compared with control (P < 0.05). More importantly, WB and LP + WB treatments significantly reduced the pH value and NH3-N concentration, and increased lactic acid content (P < 0.05). Microbial analysis indicated that the bacterial community in WB and LP + WB treatments showed distinct difference with LP and control. Lactobacillus was the dominant genera in all treatments. However, at the species level, Lactobacillus farciminis became the most dominant bacteria in control and LP treatments while the dominant bacteria in WB and LP + WB were Lactobacillus brevis and Lactobacillus farciminis. In addition, Lactobacillus brevis was positively correlated to crude protein and lactic acid and negatively correlated to pH and NH3-N. Overall, this study revealed that ensiling paper mulberry with WB or combination LP could improve silage quality through altering microbial community, which provided a practical approach for enhancing paper mulberry silage quality. Conclusion Wheat bran and combinations of Lactobacillus plantarum and wheat bran additions could reduce pH, NH3-N and increase LA content. The application of WB and LP + WB shifted the dominant bacteria species to Lactobacillus brevis. In summary, the addition of wheat bran and combinations of lactic acid bacteria and wheat bran were effective ways to enhance paper mulberry silage fermentation. Graphical Abstract